ANALYSIS OF FINANCIAL PERFORMANCE PT. SALIM IVOMAS PRATAMA, TbkANALYSIS OF FINANCIAL PERFORMANCE PT. SALIM IVOMAS PRATAMA, Tbk - Dwilita, Handriyani (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2019)
Financial performance is one measure or assessment of the success of a company's management. The measurement of financial performance assessment in this study uses financial ratio analysis. This study aims to assess the financial performance of PT.Salim Ivomas Pratama Tbk as seen from the ratio of debt to equity, debt to assets, total assets turn over, return on investment and return on equity. The analysis used is descriptive analysis to provide an overview and interpretation of research objects with existing reality. The research sample uses the financial statements for the period 2010 to 2016. The research results note that the analysis of the solvency ratio measured from Debt to Equity and debt to Asset is solvable (safe). The ratio of company activity measured based on the ratio of total asset turnover is still in the good category even though during the period 2010-2016 the total asset turnover of the company experienced fluctuations. While the profitability ratio measured by the ratio of return on investment and return on equity tends to decrease.